Genetic Differentiation of Reintroduced Père David’s Deer (Elaphurus davidianus) Based on Population Genomics Analysis - Zhang, Shumiao; Li, Chao; Li, Yiping; Chen, Qi; Hu, Defu; Cheng, Zhibin; Wang, Xiao; Shan, Yunfang; Bai, Jiade; Liu, Gang (Frontiers in Genetics, 2021)
The reintroduction success has been variable across species or regions, and it is relatively low due to different factors. Genetic evaluation is important to the conservation management of reintroduced species. Genetic concerns are associated with small populations or severely historically bottle-necked species, such as loss of genetic diversity and inbreeding. Small populations are susceptible to genetic drift and fixation, and these phenomena can be accelerated by in-breeding in Père David's deer (Elaphurus davidianus). However, the reintroduction populations were not detected in terms of genetic diversity and genetic structure. Genomics techniques were used to reconstruct population histories and estimate contemporary levels of genetic variation and gene flow among captive, free-ranging and wild populations of Père David’s deer. The hypothesis was tested that the captive population in Beijing Père David’s deer park is differentiated from the populations in Jiangsu Dafeng National Nature Reserve. The results showed that the low level of genome-wide genetic diversity was observed in Père David's deer compared with Red deer and Sika deer. A moderate population genetic differentiation was detected among three populations of Père David's deer, especially between captive and free-ranging populations, and the effective population size of Père David's deer started to decline ~25.8 ka. The findings of this study could highlight the necessity of individual exchange between different facilities.